Riddah Perspektif Islam Dalam Kajian Tafsir Ayat Al-Ahkam (Analisis Kata Riddah Dalam Nash Al-Quran) - Herfin Fahri (LPPM Institut Agama Islam Al-Hikmah Tuban, 2019)
Abstract, Some literary studies state that deeds of riddah are not merely changing religions from one religion to another, but are a major criminal act against Muslims. According to Islam, deeds of riddah not only change their mind from one religion to another but change the loyalty from one sovereignty to another. In other words, from a Muslim community or country to a non-Muslim country. Broadly speaking, acts of riddah or apostasy become two categories. The first category of apostates who invite others to apostasy and the second category of apostates who are silent. Acts of riddah or apostasy including immoral acts and threatened by God with sin and punishment in the hereafter. God forbid acts of riddah because these actions violate one of the joints of human life (daru>riyya>t five), namely religion, which means keeping religion highly prioritized namely hifd al-di>n. The firmness of Allah's prohibition on riddah or apostasy is explained in the QS. Al-Baqarah verse 217.Keywords: riddah, Islamic perspective, interpretation of aya> t al-ahka>m, Texts of the Qur'an.